The Qur'an's View of Career Women: Analysis of Sheikh Nawawi Al-Bantani's Interpretation in Tafsir Marāh Labīd - Sofwan Mabrur; Tarto; Unggul Prayoga (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study examines the Qur'anic perspective on career women based on the interpretation of Sheikh Nawawi Al-Bantani in his work Tafsir Marāh Labīd. As a 19th-century Nusantara scholar, Nawawi offers a distinctive approach that harmonizes classical Islamic scholarship with the socio-cultural realities of the Indonesian archipelago. Using a qualitative library research method with content analysis, this study explores three main themes: women's roles in politics (QS. An-Naml: 29–35), women's opportunities to excel (QS. An-Nisā': 32), and women's rights to pursue careers (QS. Ali 'Imrān: 195). The findings reveal that Nawawi does not prohibit women from public leadership, as exemplified by his appreciation of Queen Balqis's political wisdom. He affirms spiritual equality between men and women in terms of reward for deeds while acknowledging contextual, functional role differences. Moreover, Nawawi emphasizes that righteous work (amal ṣāliḥ) is not limited by gender, and women have the right to work and achieve as long as they adhere to Islamic principles and, for married women, maintain marital harmony. This interpretation provides a theological foundation for gender equality within the framework of Sharia, bridging traditional Islamic values and contemporary demands for women's empowerment.